Elaboración de planes, programas y estratégias de cambio climático en el Gad de Cotopaxí. - Reatiqui Acurio, María Belén (2017)
The effects of the climate change that is generated in different parts at Cotopaxi Province are now evident, this is due to the presence of multiple factors that intervene and contribute in an accelerated way to climate change this project objective was the elaboration of climate change plans, programs, and strategies for Departament of Environment at Cotopaxi Decentralized Autonomous Government. For its development, relevant information was collected from institutions such as the Ecuador Ministry of Environment, National Institute of Meteorology and Hydrology and Secretary of Risks Management. The research was developed in the seven cantons of the province: La Maná, Sigchos, Latacunga, Pangua, Pujilí, Salcedo and Saquisilí where it was possible to identify the most latent threats that were produced: floods, landslides, frosts and forest fires. This allowed defining strategies, plans and mitigation programs to prevent the risks associated with climate change. Description matrices were elaborated in which measures are taken against the climate change effects. Through the established proposal to prevent and mitigate possible risks of climate change in the most vulnerability areas in the Province. It will reduce the social and environmental responsibility of the control entities and strengthen the link for adequate risks management. Keywords: Threats, Vulnerability, Strategy, Measures, Mitigation, Plans